IMPLEMENTASI NILAI-NILAI MULTIKULTURAL DALAM PEMBELAJARAN PENDIDIKAN PANCASILA DI UNIVERSITAS AL ASYARIAH MANDAR - Hasbullah, Hasbullah; Najamuddin, Najamuddin; Mustari, Mustari (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2024)
University Al Asyariah Mandar is considered a miniature of Indonesia because its students come from various regions in Indonesia. The cultural and religious diversity at this university makes it known as a multicultural campus. Multicultural values refer to a set of principles, beliefs, norms, and behaviors that promote respect for the diversity of cultures, ethnicities, religions, languages, and other backgrounds in a society. Pancasila education is considered an important subject for instilling multicultural values in students. Pancasila education is a subject that shapes students' character and personality, reflecting the spirit of unity in diversity. Therefore, it is necessary to implement multicultural values through learning Pancasila education at Al Asyariah Mandar University. In this research, the type of research used is descriptive research with a qualitative approach. Data collection is carried out by interviews, observation, or document analysis. The results of this research show that the implementation of multicultural values in learning Pancasila education at Al Asyariah Mandar University involves planning, implementation and evaluation as the main stages. This approach is supported by the use of Skinner's operant conditioning theory to shape student behavior by providing positive reinforcement related to multicultural attitudes. Even though systematic planning efforts have been made through the Semester Learning Plan (RPS), the implementation of learning is still faced with several obstacles, including student awareness and readiness, student characteristics, and limited learning facilities and infrastructure.